Emerging graphitic carbon nitride-based membranes for water purification. (15th July 2021) - Cui, Yuqi; An, Xiaoqiang; Zhang, Shun; Tang, Qingwen; Lan, Huachun; Liu, Huijuan; Qu, Jiuhui
Highlights: Recent advances of g-C3 N4 -based membranes for water purification are reviewed. Regulation strategies of g-C3 N4 molecules for membrane preparation are discussed. Fabrication and applications of the state-of-the-art membranes are summarized. g-C3 N4 with multifunctional properties is extremely potential in membrane development. Challenges and prospects of g-C3 N4 -based membranes for water treatment are proposed. Abstract: Membrane separation is a promising technology that can effectively remove various existing contaminants from water with low energy consumption and small carbon footprint. The critical issue of membrane technology development is to obtain a low-cost, stable, tunable and multifunctional material for membrane fabrication. Graphitic carbon nitride (g-C3 N4 ) has emerged as a promising membrane material, owing to the unique structure characteristics and outstanding catalytic activity. This review paper outlined the advanced material strategies used to regulate the molecule structure of g-C3 N4 for membrane separation. The presentative progresses on the applications of g-C3 N4 -based membranes for water purification have been elaborated. Essentially, we highlighted the innovation integration of physical separation, catalysis and energy conversion during water purification, which was of great importance for the sustainability of water treatment techniques. Finally, the continuing challenges of g-C3 N4 -based membranes and the possible breakthrough directions in the future research was prospected.